2012
DOI: 10.1097/yct.0b013e31824a47ca
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electroconvulsive Stimulation on Long-Term Potentiation and Synaptophysin in the Hippocampus of Rats With Depressive Behavior

Abstract: These results suggest that ECS can reverse the harmful behavioral effects of CUMS in rats and that the behavioral alterations induced by ECS and/or CUMS may be associated with hippocampal neuroplasticity and SYP levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…However, they found that CMS exposure facilitated CA1 LTD (Holderbach et al, 2007). On the other hand, Li et al (2012) exposed rats to 4 weeks of chronic unpredictable stress (CUMS) and 1 week later found impaired LTP in the CA1. The difference between the findings could result from the fact that we measured LTP in the NAc or because the CUMS involves the use of various physical and psychological stressors in a predetermined manner so that the animal is not able to adapt to the stressor.…”
Section: Cms and Win55212-2 Effects On Plasticitymentioning
confidence: 99%
“…However, they found that CMS exposure facilitated CA1 LTD (Holderbach et al, 2007). On the other hand, Li et al (2012) exposed rats to 4 weeks of chronic unpredictable stress (CUMS) and 1 week later found impaired LTP in the CA1. The difference between the findings could result from the fact that we measured LTP in the NAc or because the CUMS involves the use of various physical and psychological stressors in a predetermined manner so that the animal is not able to adapt to the stressor.…”
Section: Cms and Win55212-2 Effects On Plasticitymentioning
confidence: 99%
“…Using rats neonatally-exposed to clomipramine as an animal model of depression, Bhagya et al [134] found that these animals displayed a decreased LTP in the hippocampal CA1 and a 14-day treatment with the SSRI escitalopram restored this LTP. Similarly, retrieval of LTP in the CA1 field of hippocampus was obtained in stressed animals after repeated application of other classes of ADs including the SNRI milnacipran and electroconvulsive stimulation (ECS) [132,135]. In contrast, other groups described an impairment of LTP after chronic SSRI fluoxetine, TCA imipramine, SNRI venlafaxine or ECS, but in non-stressed animals [136][137][138], indicating a stress-dependent action of the ADs on hippocampal LTP.…”
Section: Synaptic Plasticity and Synaptogenesismentioning
confidence: 95%
“…Synaptic communication is altered by chronic stress which impairs LTP and facilitates LTD induction in the CA1 of the hippocampus [131][132][133]. It has been reported that repeated application of the SSRI fluvoxamine (21 days) increased the extent of LTP induction in the CA1 region of rats that experienced chronic mild stress [131].…”
Section: Synaptic Plasticity and Synaptogenesismentioning
confidence: 99%
“…9,17 The rats received daily stimuli for 4 weeks. Stressors consisted of the following conditions: food deprivation for 24 hours, water deprivation for 24 hours, swimming in cold water 4-C for 5 minutes, swimming in hot water (45-C) for 5 minutes, shaking for 15 minutes (1 shake/s), tail pinching for 1 minute, 24 hours of continuous lighting, housing in a soiled cage for 24 hours, or cage titling to 45 degrees for 24 hours.…”
Section: Animals and Cumsmentioning
confidence: 99%